Analysis of Flood Disaster Mitigation Policy in Lamongan District - Achmad Aufa Anggarda; Hartuti Purnaweni; Sri Suwitri; Teuku Afrizal (International Journal of Social Science and Business, 2021)
Flood is a frequent disaster in Indonesia, so it is an important public administration problem to overcome. This study aims to determine the flood disaster mitigation policy in Lamongan Regency. By knowing and analyzing this flood disaster mitigation policy, alternative policies are prepared that can be recommendations for the Lamongan Regency Government, especially the Regional Disaster Management Agency. Determination of policy alternatives uses 5 (five) stages in policy analysis according to Brigman & Davis, namely formulating problems in policy, determining goals and objectives, determining policy parameters, seeking policy alternatives, and deciding alternative options. The purpose of this study is to formulate and determine the best policy alternatives to overcome problems in the implementation of flood disaster mitigation in the Lamongan Regency. The research method is carried out by analyzing data through supporting documents, journals, books, and other references. The study results indicate that current policy problems have not led to flood disaster mitigation, but rather 'wait' until the flood disaster occurs, then the Government and BPBD Lamongan Regency only act by assisting flood victims. The proposed alternative policy is the prevention, handling, and recovery of flood disaster mitigation in the Lamongan Regency area with community participation.